Reforming Islamic Family Law: The Relevance of Ibn Qayyim al-Jawziyyah's Concept of Legal Change - Ayu Sari Ningsih; Nawa Angkasa; Nency Dela Oktora; Sakirman Sakirman; Nyimas Lidya Putri Pertiwi; Ananto Triwibowo (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2025)
Ibn Qayyim al-Jawziyyah's concept of legal change—asserting that Islamic law can evolve in response to variations in place, time, conditions, motives, and customs—offers a foundational framework for contemporary Islamic legal thought. This principle provides significant theoretical support for the ongoing renewal of Islamic family law. This study aims to critically examine the implementation of Ibn Qayyim's legal change theory in the reform of Islamic family law to meet the demands of modern social contexts. Using a library research method and a doctrinal-deductive approach, this study analyzes classical and contemporary texts to extract relevant insights. Data collection was conducted through document analysis, and triangulation of sources was employed for validation. The findings reveal that Ibn Qayyim's theory is not only relevant but essential to the dynamic nature of Islamic family law, particularly in responding to social transformations and preventing legal stagnation. His approach enables the contextualization of legal rulings, thereby aligning them with contemporary realities without detaching from Islamic legal principles. The study contributes to the discourse on Islamic legal reform by offering a normative-empirical argument for adapting Islamic family law to changing societal needs. It underscores the legitimacy of legal flexibility within Islamic jurisprudence and advocates for a responsive, contextualized approach to lawmaking. By grounding reform in social reality, this study affirms that differences and changes in Islamic family law are not only inevitable but also necessary for its continued relevance and justice in the modern world.